2014
DOI: 10.1371/journal.pcbi.1003601
|View full text |Cite
|
Sign up to set email alerts
|

Combined Role of Seizure-Induced Dendritic Morphology Alterations and Spine Loss in Newborn Granule Cells with Mossy Fiber Sprouting on the Hyperexcitability of a Computer Model of the Dentate Gyrus

Abstract: Temporal lobe epilepsy strongly affects hippocampal dentate gyrus granule cells morphology. These cells exhibit seizure-induced anatomical alterations including mossy fiber sprouting, changes in the apical and basal dendritic tree and suffer substantial dendritic spine loss. The effect of some of these changes on the hyperexcitability of the dentate gyrus has been widely studied. For example, mossy fiber sprouting increases the excitability of the circuit while dendritic spine loss may have the opposite effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Therefore, it is possible that this high sensitivity to excitotoxicity leads to loss of neurons and spines in the hippocampus of PTD mice. Moreover, seizures and neurodegenerative diseases such as Alzheimer’s disease causes dendritic spine abnormality including spine loss in the DG neurons, 68–70 ) raising the possibility that dendritic spines in DG neurons are susceptible to pathological damages by PTD. It is important to examine whether neural degeneration at the cellular, synaptic, and spine levels occurs in the hippocampus of WKS cases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that this high sensitivity to excitotoxicity leads to loss of neurons and spines in the hippocampus of PTD mice. Moreover, seizures and neurodegenerative diseases such as Alzheimer’s disease causes dendritic spine abnormality including spine loss in the DG neurons, 68–70 ) raising the possibility that dendritic spines in DG neurons are susceptible to pathological damages by PTD. It is important to examine whether neural degeneration at the cellular, synaptic, and spine levels occurs in the hippocampus of WKS cases.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal basal dendrites form additional recurrent synapses with the aberrant axonal collaterals of the MF, thus aggravating the recurrent nature of the circuit (Patel et al, 2004 ). Although not all the experimental data support the idea of individual cell hyper-excitability in epilepsy (Patel et al, 2004 ), computational (Tejada et al, 2012 , 2014 ) and in vitro (Beck et al, 1996 ; Bausch and McNamara, 2000 ) models do strongly reinforce this notion. In addition, the electrophysiological properties of granule cells aberrantly located in the hilar region were studied in a rat model of TLE and in epileptic patients by Althaus et al The authors found an increased excitability in rat neurons whereas neurons obtained from patients displayed a clear reduction in excitability.…”
Section: Regulation Of the Morphology Of Newborn Granule Neurons By Dmentioning
confidence: 98%
“…In the SGZ, newly born neurons migrate into the DG granule cell layer and mature, connecting it with the CA3 region of the hippocampus. The influence of immature granular cells (ImN) on network performance was implemented according to the model of posttraumatic DG activity [6]. It follows that the increase of the number of newborn granular neurons enhances network excitability, and, thus, newborn neuron loss following irradiation will likely suppress the network activity.…”
Section: Hippocampal Neural Networkmentioning
confidence: 99%